2017
DOI: 10.1021/acs.jproteome.6b00974
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Interplay of Fungi, Algae, and Bacteria within the Lung Lichen Lobaria pulmonaria L. Hoffm. as Assessed by State-of-the-Art Metaproteomics

Abstract: Lichens are recognized by macroscopic structures formed by a heterotrophic fungus, the mycobiont, which hosts internal autotrophic photosynthetic algal and/or cyanobacterial partners, referred to as the photobiont. We analyzed the structure and functionality of the entire lung lichen Lobaria pulmonaria L. Hoffm. collected from two different sites by state-of-the-art metaproteomics. In addition to the green algae and the ascomycetous fungus, a lichenicolous fungus as well as a complex prokaryotic community (dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 61 publications
1
44
0
1
Order By: Relevance
“…Several roles of lichen-associated bacteria have been suggested and include nutrient supply (e.g., by nitrogen fixation and phosphate scavenging), nutrient recycling, protection against UV radiation, resistance to abiotic and biotic environmental stressors, and thallus degradation ( Eymann et al, 2017 ). Unlike terrestrial lichens, marine lichens would need to be adapted to much more variable gradients of UV light, salinity (osmotic) stress, heat, desiccation and mechanical stresses from wave action and therefore we would expect the associated bacteria to play a role in resisting these particularly variable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several roles of lichen-associated bacteria have been suggested and include nutrient supply (e.g., by nitrogen fixation and phosphate scavenging), nutrient recycling, protection against UV radiation, resistance to abiotic and biotic environmental stressors, and thallus degradation ( Eymann et al, 2017 ). Unlike terrestrial lichens, marine lichens would need to be adapted to much more variable gradients of UV light, salinity (osmotic) stress, heat, desiccation and mechanical stresses from wave action and therefore we would expect the associated bacteria to play a role in resisting these particularly variable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various lichen-associated bacteria can provide essential nutrients to the symbiosis ( Sigurbjörnsdóttir et al, 2015 ). These and various other findings related to the composition and functioning of the lichen microbiota contribute to the accumulating evidence that bacteria other than cyanobionts are an essential part of the symbiosis ( Hodkinson and Lutzoni, 2009 ; Cardinale et al, 2012 ; Hodkinson et al, 2012 ; Aschenbrenner et al, 2016 ; Eymann et al, 2017 ). The identified ancillary mechanisms provided by highly abundant and diversified microorganisms contribute to the persistence and longevity of the lichen symbiosis ( Grube et al, 2015 ).…”
Section: Introductionmentioning
confidence: 63%
“…Such adaptations facilitate persistence of the microbiota and thus might be crucial to preserve symbiosis-relevant functioning (Figure 5 ). By enduring unfavorable conditions in typical lichen habitats, which primarily include high fluctuations in humidity and temperature, the associated bacteria can fulfill their main roles as (i) protectors against biotic and abiotic stresses, (ii) providers of nutrients, vitamins and co-factors, and (iii) detoxifiers of organic and inorganic compounds ( Grube et al, 2015 ; Cernava et al, 2017 ; Eymann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metaproteome analysis of L. pulmonaria also supports the hypothesis. Eymann et al [26] established that the functional diversities of the symbionts of L. pulmonaria assist the lichen in longevity.…”
Section: Verification and Expression Of Pha M C L Synthase-encoding Genementioning
confidence: 99%
“…Besides the elimination of stress, the lichen-associated microbiomes showed evidence in the detoxification of inorganic and organic matters such as arsenic, copper, and zinc as well as xenobiotic/PAH substances [24,25]. Moreover, a comprehensive proteomic study on lung lichen Lobaria pulmonaria showed that bacterial enzymes identified from L. pulmonaria are responsible for the metabolism of methanol/C1compounds and CO-detoxification [26]. On the other hand, it has been strongly believed that PHA synthesis is one of the survival mechanisms of the bacteria to live in stressful and unstable environments [27].…”
Section: Introductionmentioning
confidence: 99%